2010
DOI: 10.1021/cn1000843
|View full text |Cite
|
Sign up to set email alerts
|

Central Processing of the Chemical Senses: An Overview

Abstract: Our knowledge regarding the neural processing of the three chemical senses has been lagging behind that of our other senses considerably. It is only during the last 25 years that significant advances have been made in our understanding of where in the human brain odors, tastants, and trigeminal stimuli are processed. Here we provide an overview of the current knowledge of how the human brain processes chemical stimuli based on findings in neuroimaging studies using positron emission tomography and functional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(177 citation statements)
references
References 97 publications
(132 reference statements)
6
169
1
1
Order By: Relevance
“…The sensory characteristics of food (taste, odors and texture) are also important in food choice, and these can be well studied by fMRI (39). Visual attention can be rapidly cued by food items -particularly items with high calorific content, and attentional responding to these is magnified in overweight individuals, suggesting that heightened attention to high-caloric food cues promotes greater intake.…”
Section: Emotions and Decision-makingmentioning
confidence: 99%
“…The sensory characteristics of food (taste, odors and texture) are also important in food choice, and these can be well studied by fMRI (39). Visual attention can be rapidly cued by food items -particularly items with high calorific content, and attentional responding to these is magnified in overweight individuals, suggesting that heightened attention to high-caloric food cues promotes greater intake.…”
Section: Emotions and Decision-makingmentioning
confidence: 99%
“…Recently it has been suggested that, whereas the piriform cortex processes the initial stage of the formation of an odor quality percept (Lundström et al, 2011), the orbitofrontal cortex (OFC) is responsible for the final quality decision. Of particular relevance to the present work is a neuroimaging study (Savic et al, 2000) demonstrating that the OFC was activated during an odor quality discrimination task and not during an odor intensity discrimination task.…”
Section: Possible Anatomical Basis Of Visual-olfactory Crossmodal Intmentioning
confidence: 99%
“…Of course, once ingestion has started, gastrointestinal neural and hormonal signals also start to contribute. Summaries and detail on the basic processing of food stimuli in the brain can be found in several reviews and meta-analyses addressing visual food stimuli (food images) (9) , odour (10) , taste (11,12) and flavour (taste, odour and somatosensory stimulation) (13,14) . A well-known phenomenon driven by cephalic stimulation is sensory-specific satiety (15) .…”
Section: Food-brain Interactionmentioning
confidence: 99%